Bacteriophage-mediated manipulations of microbiota in gastrointestinal diseases - El Haddad, Lynn; Mendoza, Jesus F.; Jobin, Christian (Frontiers in Microbiology, 2022)
Although some gastrointestinal diseases could be managed using various antibiotics regimen, this therapeutic approach lacks precision and damages the microbiota. Emerging literature suggests that phages may play a key role in restoring the gut microbiome balance and controlling disease progression either with exogenous phage intervention or filtered fecal transplantation or even engineered phages. In this review, we will discuss the current phage applications aiming at controlling the bacterial population and preventing infection, inflammation, and cancer progression in the context of gastrointestinal diseases.